The association of follicle stimulating hormone receptor (FSHR) gene polymorphism of on egg productivity in hybrid chicken (Gallus gallus gallus, Linnaeus 1758) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Kurnia RR, Lesmana I, Ernanto AR, Perdamaian ABI, Trijoko, Daryono BS. 2021. The association of follicle stimulating hormone receptor (FSHR) gene polymorphism of on egg productivity in hybrid chicken (Gallus gallus gallus, Linnaeus 1758). Biodiversitas 22: 1221-1226. Pelung chicken genetics Improvement by selective breeding to Layer Lohmann Brown was successfully developed F1 which yielded 140 eggs for 300 days of production. BC1 chicken derived from ? Layer and ? F1 (? Layer vs ? Pelung chicken). Polymorphism on cFSHR gene promoter was potential genetic marker candidate to assist the selection. This research aims to study the BC1 chicken egg-related traits performance for 16 weeks and study the correlation of cFSHR polymorphism to egg productivity. FSHR gene promoter was showed using sanger sequencing. Chicken were grouped based on their haplotype. Chicken were maintained in battery cage for observation of egg production. The results show that there is a difference of BC1 chicken DOC weight from different egg weight. The six SNP polymorphisms exist on cFSHR gene promoter fragments on 10, 51, 59, 121, 233, 331 nucleotides and conducted 7 haplotype group. The highest egg production in BC1 chicken on TTGCYA and lowest egg production on TTGYYG haplotype. Based on the correlation test there was a positive correlation at p> 0.05 between BC1 chicken TTGCYA haplotype with egg production and positive correlation at p
Keywords: backcross, cFSHR gene promoter, egg productivity, hybrid chicken